Solution:
Given
![](https://1.bp.blogspot.com/-sx9HHHIC3To/XvNlOpaoeGI/AAAAAAAADXI/Dc9kt2_cM0c0Lr5AUdcoJk-YAinULHJ-gCK4BGAsYHg/w320-h105-rw/1.gif)
Again
X + Y = 0
Multiply by 2 on both side
![](https://1.bp.blogspot.com/-GedMWFGKwzM/XvNrICGIzTI/AAAAAAAADXk/9fdopOeYcRMJQt8bceFo-BQ86HhA4UB3QCK4BGAsYHg/w320-h53-rw/2.gif)
Adding equation (1) and (2)
![](https://1.bp.blogspot.com/-N4SPAiQTYnI/XvNu2ojpTOI/AAAAAAAADYA/9xBnN2oDOlgXVB_vil0F9Lvp1esVLRg1wCK4BGAsYHg/w210-h400-rw/23.gif)
Therefore X=1 , Z=3
Now putting X=1, Z=3 in equation (1)
X - 2Y = Z
1 - 2Y = 3
2Y = 4
Y = 4/2
Y = 2
Therefore X : Y : Z = 1 : 2 : 3
Given
![](https://1.bp.blogspot.com/-sx9HHHIC3To/XvNlOpaoeGI/AAAAAAAADXI/Dc9kt2_cM0c0Lr5AUdcoJk-YAinULHJ-gCK4BGAsYHg/w320-h105-rw/1.gif)
Again
X + Y = 0
Multiply by 2 on both side
![](https://1.bp.blogspot.com/-GedMWFGKwzM/XvNrICGIzTI/AAAAAAAADXk/9fdopOeYcRMJQt8bceFo-BQ86HhA4UB3QCK4BGAsYHg/w320-h53-rw/2.gif)
Adding equation (1) and (2)
![](https://1.bp.blogspot.com/-N4SPAiQTYnI/XvNu2ojpTOI/AAAAAAAADYA/9xBnN2oDOlgXVB_vil0F9Lvp1esVLRg1wCK4BGAsYHg/w210-h400-rw/23.gif)
Therefore X=1 , Z=3
Now putting X=1, Z=3 in equation (1)
X - 2Y = Z
1 - 2Y = 3
2Y = 4
Y = 4/2
Y = 2
Therefore X : Y : Z = 1 : 2 : 3
Tags:
Advance Math Class 8